Types of anemia in hematological malignancy - Al-Jameel, Imran (International Journal of Research in Medical Sciences, 2025)
Background: Anemia is a condition where a person's hemoglobin or red blood cells (RBC) levels are inadequate. This disease affects about one-third of the population of the world. Anemia has been linked to higher morbidity and mortality rates in patients with hematological malignancies. This study aimed to investigate the causes and types of anemia in a group of patients with hematological malignancies at Hiwa Cancer Center, Sulaymaniyah, Iraq. Methods: A total of 41 patients diagnosed with hematological malignancy were recruited. Relevant patient information was gathered. Their records, including demographic data, complete blood count (CBC) findings at presentation, blood films, and bone marrow slides, were reviewed and recorded. Furthermore, erythrocyte sedimentation rate, reticulocytes count, Coombs test, iron status, prothrombin time (PT), and activated partial thromboplastin time (APTT) were evaluated. Results: Data of this study showed that the most prevalent hematological malignancy in 41 patients was chronic lymphocytic leukemia (24.4%) and the less prevalent form was multiple myeloma (5%). Furthermore, in our study, results showed that the most frequent type of anemia was normocytic (76%) and the least frequent form was macrocytic anemia (7%). Conclusions: The current study proved that normocytic anemia is the most common type of anemia among patients with hematological malignancies.